Identification and validation of microsatellite markers in strawberry tree (Arbutusunedo L.) - Fazenda, Pedro (2019)
Strawberry tree (Arbutus unedo L.), an evergreen shrub/small tree of the family Ericaceae, is a main constituent of the Mediterranean basin flora; although it is also found in southwestern Prance, Macaronesia, and Ireland. The small fruits are edible but mostly used for preparation of preserves and jams, and for liquors such as the Portuguese traditional "aguardente de medronho". Traditionally cultivated by small farmers, often in consociation with Quercus sp., strawberry tree is presently emerging as a new important fruit crop cultivated in large orchards by modern export-oriented enterprises. This change of paradigm requires a growing role of plant breeding, upstream of the production process. Genomic tools for this species are mostly limited to the chloroplast genome sequence and to genomic data described in this work. In order to identify strawberry tree microsatellite (SSR) loci we performed partial genome next-generation sequencing using the Ion Torrent technology. The sequenced similar to 24.6M nucleotides resulted in the identification of 1185 microsatellite markers mostly constituted by dinucleotide motifs. The relative amount of microsatellite dinucleotide motifs (AG/CT - 71.7%, AC/GT - 20.5%, AT/AT - 2.9%, and CG/CG - 0.3%) is similar to the one observed in other Ericaceae species. Among a tested sample of 40 SSR primer pairs, 20 amplified well-defined PCR products, 12 (30%) were validated as polymorphic. Used in our collaborative project for molecular identification of selected and improved clones, the identified SSR loci constitute a strong tool for a large panoply of applied and fundamental studies of this emerging fruit crop.